The Effect of Outsourcing on Anglogold Ashanti Obuasi Mines Performance - Yeboah, Kofi Owusu; Boateng, Charles; Amponsem, Josephine; Attefah, Erick Kwaku (International Journal of Business, Economics and Management, 2015)
Competition in the modern world has forced organisations to adopt innovative ways to create value. The world has embraced the phenomenon of outsourcing and companies have adopted this principle to help them expand into other markets. Tactical management of subcontracting is perhaps the best instrument in management, and subcontracting of innovation is its frontline. The purpose of this study can be summed up as assessing outsourcing in Anglogold Ashanti Obuasi mines. This study adopted the descriptive research approach. Questionnaire was administered to staff of outsourcing department. One hundred (100) employees of AngloGold Ashanti Obuasi Mines were sampled. Quantitative data analysis technique (such as Mean, Standard deviation, confidence level, frequency, and simple percentages) and qualitative data analysis technique such as content analysis will be used to analyse collected data. Some of the activities that are outsourced are; transportation of employees to and from work, haulage of mine ore, residence maintenance, and purchase and contract unit are outsourced. In addition information technology, human resource, and management services are not outsource. It was also found out that outsourcing helps to: cut down cost; focus on core activities; generate competitive advantage; transfer operational risk; achieve efficiency and economies of scale; access expertise that is lacking in-house; and save valuable time. However outsourcing does not help AngloGold to expand and that the major reason for outsourcing at AngloGold is to help the company to focus on core activities. It was discovered that outsourcing of activities at AngloGold Ashanti Obuasi mines has not always achieved the stated objectives.